Pharmacotherapeutic follow-up in patients with type 1 diabetes in context of judicialization: possibility optimize costs - William Neves Oliveira; Maurílio Souza Cazarim; Thays Santos Mendonça; Paulo Roque Obreli-Neto; Mariana Linhares Pereira; André Oliveira Baldoni (Brazilian Journal of Pharmaceutical Sciences, 2023)
Abstract In Brazil, insulin analogs stand out as one of the most demanded medications by judicial means. However, the guarantee of judicial access does not guarantee rational use. In context, pharmacotherapeutic follow-up (PF) is shown to be clinical effective strategy for patients with diabetes. To evaluate direct medical costs one year after performing PF in patients with type 1 diabetes mellitus using insulin analogs ordered by court in Public Health System (Sistema Único de Saúde - SUS). This is a partial economic analysis, nested within a quasi-experimental study. Patients with T1DM who receive insulin analogs by judicialization in a medium-sized Brazilian city participated. The PF was conducted following the method adapted from the Pharmacotherapy workup (PW). Data were collected considering the period of one year before the start of the intervention and one year after the start of the intervention. Direct medical costs were evaluated and the difference in costs was calculated. 28 patients participated in the intervention. After PF, direct costs were -$3,696.78. Sensitivity analysis showed that there is a 33.4 % chance for PF to present cost savings when compared to baseline. The PF has the potential to reduce direct medical costs from the perspective of the SUS.